Sistem Monitoring Penghitungan Barang Otomatis Berbasis Internet of Things - Ahmad Rafli; Didik Setiyadi; Syahbaniar Rofiah (STMIK IKMI Cirebon, 2020)
Technology is something that was created to help and facilitate human work in various aspects needed for the survival and comfort of life in the company. All goods produced will be counted before distribution. The calculation and input of goods in PT Winner Pratama has not been done automatically, so the researchers solved the solution by creating an automated item counting system based on the Internet of Things and Website. This system is designed using Infrared (IR) Sensor, Nodemcu esp8266, Breadboard, Jumper cable, Buzzer, Push Button, Lcd I2c, Database, and Dcmotor. With the prototype method to simulate this system before it is applied in the production field to find out how the system works. And based on testing infrared sensors as much as 10x by means of an object closer to the sensor with a distance of 2-6 cm successfully, this system can help employees to find out the number of items automatically generated every day, without having to do the calculations manually. In addition to automatic counting, the system also performs input automatically and the data is stored in a database.